An increasing trend in daily monsoon precipitation extreme indices over Pakistan and its relationship with atmospheric circulations - Ullah, Waheed; Karim, Aisha; Ullah, Sami; Rehman, Atta-Ur; Bibi, Tehmina; Wang, Guojie; Ullah, Safi; Bhatti, Asher Samuel; Ali, Gohar; Abbas, Adnan; Hagan, Daniel Fiffi Tawia; Nooni, Isaac Kwesi; et al. (Frontiers in Environmental Science, 2023)
This study assessed spatiotemporal trends in daily monsoon precipitation extremes at seasonal and subseasonal scales (June, July, August, and September) and their links with atmospheric circulations over Pakistan. The study used observed precipitation data from fifty in-situ stations and reanalysis products from the European Centre for Medium-Range Weather Forecasts (ECMWF) and National Centers for Environmental Prediction/ the National Center for Atmospheric Research (NCEP/NCAR) during 1981-2018. A suite of seven extreme precipitation indices and non-parametric statistical techniques were used to infer trends in the frequency and intensity of extreme precipitation indices. An increase in frequency and intensity of overall extreme indices was evident, with a maximum tendency in the country's northwestern (z-score=>2.5), central, and eastern (z-score > 4) monsoon-dominant parts. The northern and southwestern parts of the country exhibited a slight decrease (z-score <-2) in frequency and intensity. The Sen's Slope estimator (SSE) shows an increase in western parts (0.20 days) indicating a shift in the maxima of the monsoon precipitation. The regional precipitation shows an increase in wet days (R1mm) with higher values of mMK (3.71) and SSE (0.3) in region 2 Similar results of moderate regional increase are evident for extreme indices except regions 1 and 3. The extreme one-day maximum precipitation increased in region 3 (mMK: 1.39, SSE: 2.32). The extremely wet days (R99p TOT) precipitation has a moderate increase in all regions with a decrease in region 1.The temporal mutations showed dynamic changes, clearly reflecting the country's historical extreme events. The frequency and intensity of precipitation extremes negatively correlated with the altitude (R= -0.00039). The probability distribution function (PDF) showed a significant increase in the density during June and September with a probabilistic positive shift during July and August. The intensified mid-latitude westerlies and subtropical zonal easterlies teleconnections, strengthening of the monsoon trough, and land-ocean thermal contrast are the potential drivers of the increasing trend in precipitation extremes. The current study could serve as a benchmark for future researchers and policymakers to devise effective mitigation strategies for sustainable development.